Physiological characters of psychrotolerant bacteria in a eutrophic bottom environment - Karim, Md Abdul; Fukami, Kimio (Dhaka University Journal of Biological Sciences, 2011)
An investigation for the isolation and identification of psychrotolerant bacteria from eutrophic bottom environment showed average temperature during winter and summer was 8 and 26°C, respectively. Six bacterial isolates were characterized in details and identified as Deleya halophila, Chromohalobacter marismortui, Erythrobacter longus, Pseudomonas perfectomarina, Marinobacter hydrocarbonoclasticus, Alteromonas undina. All isolates grew well at wide range of temperature between 5 and 30ºC and considered as psychrotolerant. Key words: Psychrotolerant bacteria; Eutrophic environment DOI: http://dx.doi.org/10.3329/dujbs.v20i1.8837 Dhaka Univ. J. Biol. Sci. 20(1): 49-56, 2011 (January)